Large-$N$ mesons - Biagio Lucini (2013)
We present an update of our project of computing the meson spectrum and decay constants in large-N QCD. The results are obtained in the quenched approximation with the Wilson fermion action for N = 2, 3, 4, 5, 6, 7 and 17 and extrapolated to infinite N. We non-perturbatively determine the renormalization factors for local quark bilinears that are needed to compute the decay constants. We extrapolate our SU(7) results to the continuum limit, employing four different lattice spacings.